HIV serodiscordant sex partners and the prevalence of human herpesvirus 8 infection among HIV negative men who have sex with men: baseline data from the EXPLORE Study. (26th May 2006) - Casper, C; Carrell, D; Miller, K G; Judson, F D; Meier, A S; Pauk, J S; Morrow, R A; Corey, L; Wald, A; Celum, C
Abstract : Objectives: Human herpesvirus 8 (HHV-8) infection is common among men who have sex with men (MSM), especially those infected with HIV, and is frequently detected in saliva. We sought to determine whether oral or anogenital contact with HIV discordant, or unknown serostatus sexual partners is associated with HHV-8 seroprevalence among HIV negative MSM. Methods: HIV negative MSM participating in a behavioural intervention trial for the prevention of HIV infection (the EXPLORE study) were recruited from the Seattle and Denver areas for participation in this cross sectional study. Participants completed detailed questionnaires regarding sexual behaviour, focusing on activities with possible exposure to the oropharynx. Serum samples from study enrolment were tested for the presence of HHV-8 antibodies using whole virus enzyme immunoassay and immunofluorescence assay to latent and lytic proteins. Results: 198/819 MSM (24.3%) were HHV-8 antibody positive. Exposure to saliva with HIV positive and HIV unknown serostatus sex partners was reported by 83% and 90% of all men, respectively. In a multivariate model, reporting more than the median number of lifetime sex partners (OR 2.2, p = 0.03) or lifetime sex partners of unknown HIV status (OR 1.7, p = 0.03), and the performance of oro-anal sex ("rimming") on partners whose HIV status is unknown (OR 2.7, p = 0.04) were independently associated with HHV-8 infection. Conclusions: The oropharynx may be an important anatomical site in HHV-8 acquisition, and contact with HIV serodiscordant or unknown sex partners is associated with higher HHV-8 seroprevalence among HIV negative MSM.